2014
DOI: 10.1021/ja500027v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inert Tails on the Thermodynamics of DNA Hybridization

Abstract: The selective hybridization of DNA is of key importance for many practical applications such as gene detection and DNA-mediated self-assembly. These applications require a quantitative prediction of the hybridization free energy. Existing methods ignore the effects of non-complementary ssDNA tails beyond the first unpaired base. We use experiments and simulations to show that the binding strength of complementary ssDNA oligomers is altered by these sequences of non-complementary nucleotides. Even a small numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 25 publications
4
83
0
Order By: Relevance
“…However this modelling choice is far from being univocal. On the one hand, it has been demonstrated that the presence of inert DNA tails emanating from the duplexes, like the dsDNA spacers in the present system, can have substantial destabilising effect 18,[75][76][77]. On the other hand, Cy3 and Cy5 fluorophores have a stabilising effect, decreasing the hybridisation free energy by ≈ 2 kJ mol −1 .…”
mentioning
confidence: 73%
“…However this modelling choice is far from being univocal. On the one hand, it has been demonstrated that the presence of inert DNA tails emanating from the duplexes, like the dsDNA spacers in the present system, can have substantial destabilising effect 18,[75][76][77]. On the other hand, Cy3 and Cy5 fluorophores have a stabilising effect, decreasing the hybridisation free energy by ≈ 2 kJ mol −1 .…”
mentioning
confidence: 73%
“…12, ∆G 0 AB is the complexation free energy of the linkers free in solution, which depends on their chemical details and is usually determined experimentally or via atomistic simulations. When considering DNA oligomers ∆G 0 AB is calculated using the nearest-neighbour thermodynamic model [23,24,[147][148][149], possibly corrected for the presence of dangling DNA tails [44,149]. ∆G conf AB (h) describes the additional constraints that surface-tethered linkers experience whenever they form a complex, as compared to the same complex formed by untethered linkers [144,145].…”
Section: Figurementioning
confidence: 99%
“…The three types of modifications accordingly provide the following interactions: a mixed attraction and repulsion between all particles types ('blending') instead of repulsion-only and attraction-only as in the mother phase; predominant interparticle attraction ('stapling'); and predominant repulsion between neighbouring particles ('repelling'). Although the interaction-shifting does not depend on specific sequences, as long as input DNA strands fulfil their designated roles, the magnitude of the interaction shift may depend on the DNA length 29,30 , melting temperature, and the inert DNA tails 31 .…”
Section: Selective Lattice Transformations By Modifying Dna Shellmentioning
confidence: 99%